Relationship between serum brain-derived neurotrophic factor and cognitive impairment in children with sleep-disordered breathing - Feng, Yani; Ma, Lina; Chen, Xi; Zhang, Yitong; Cao, Zine; Yuan, Yuqi; Xie, Yushan; Liu, Haiqin; Shi, Yewen; Ren, Xiaoyong (Frontiers in Pediatrics, 2023)
Background: As an important neuroprotective factor, the brain-derived neurotrophic factor (BDNF) may have a key role in cognitive impairment in children with sleep-disordered breathing (SDB). The main aim of this study was to compare the levels of BDNF and tyrosine kinase receptor B (TrkB) in normal children and those with obstructive sleep apnea (OSA) and primary snoring (PS) and to explore a possible link between BDNF/TrkB, inflammation, and SDB with cognitive impairment in children. Methods: A total of 44 OSA children and 35 PS children who completed polysomnography between October 2017 and October 2019 were enrolled. At the same time, 40 healthy children during the same period were included as a control. Enzyme-linked immunosorbent assay was used to measure serum indices of BDNF, TrkB, interleukin-1beta (IL-1β), and tumor necrosis factor-alpha (TNF-α). Correlation and pooled analyses were performed between the cognitive scores and four serological indicators. Logistic regression was used to analyze the risk factors for cognitive impairment. Results: Significant differences were found in serum BDNF, TrkB, IL-1β, and TNF-α between the three groups (all P < 0.01). The serum BDNF and TrkB in the OSA and PS groups were lower than those in the control group, whereas the serum IL-1β and TNF-α were higher than those in the control group (all P < 0.05). Moreover, among these four indices, the strongest correlation was found between BDNF and the Chinese Wechsler Intelligence Scale (all P < 0.05). Logistic regression analysis revealed a correlation between OSA status, TrkB, and course of mouth breathing and cognitive status. Conclusion: The levels of serum BDNF and TrkB were related to cognitive impairment in children with SDB. Also, BDNF and TrkB could be used as noninvasive and objective candidate markers and predictive indices of cognitive impairment in children with SDB.